Myoepithelial carcinoma of the tongue- spindle cell morphology with high mitosis: A case report and review of literature - Abhimanyu Sharma; Priyanka Gogoi; Vinod Kumar Arora (Wolters Kluwer Medknow Publications, 2017)
Myoepithelial carcinomas represent <1% of salivary gland tumors. Tongue is a rare site of occurrence. We present a case of a 30 year old female with myoepithelial carcinoma seen over dorsum of tongue with predominantly spindle cell morphology with clear cytoplasm and mitotic count of 6-7/10 hpf. We need to differentiate it from a spindle cell squamous cell carcinoma which can be seen at this location, i.e., tongue. In our case, there was no connection of the tumor with overlying squamous epithelium.